2010
DOI: 10.3109/17435390903576451
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles up-regulate Connexin43 expression and increase gap junctional intercellular communication in human lung adenocarcinoma cell line A549

Abstract: Silver nanoparticles (Ag NPs) are increasingly being used in wound dressings, medical settings, and various household products due to their unique properties and antimicrobial activity. Despite the widespread use of Ag NP products, the molecular mechanisms underlying the biological effects of Ag NPs remain unclear. Gap junctional intercellular communication (GJIC), formed by the connexin protein family, plays a critical role in the maintenance of tissue and organ homeostasis. This study was undertaken to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 30 publications
4
8
0
Order By: Relevance
“…We observed a great increase in GJIC after AgNP treatment and this response increased with the concentration of AgNPs. This is consistent with a previous study in the human lung adenocarcinoma cell line (Deng et al, ). GJIC increases have been suggested as a chemopreventive strategy and protection against cancer development (Trosko & Chang, ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…We observed a great increase in GJIC after AgNP treatment and this response increased with the concentration of AgNPs. This is consistent with a previous study in the human lung adenocarcinoma cell line (Deng et al, ). GJIC increases have been suggested as a chemopreventive strategy and protection against cancer development (Trosko & Chang, ).…”
Section: Discussionsupporting
confidence: 94%
“…Scientists have grappled with the ion–NP question over the past few years; however, it remains uncertain whether nano‐silver or ionic‐silver is more toxic. In our previous study, we tried to investigate GJIC and Cx43 expression in human lung adenocarcinoma cells exposed to AgNPs and its released silver ion and found that different concentrations of silver ion failed to change GJIC and the expression of Cx43, indicating the effects of AgNPs were independent of silver ion in this case (Deng et al, ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, an influence of silver nanoparticles on the gap junctions of A549 cells was observed by Deng et al (2010) and morphological changes due to silver nanoparticle and silver ion incubation were also observed by others (Kawata et al, 2009;Liu et al, 2010;Nowrouzi et al, 2010). Beside the cell-cell contacts, the cellmatrix contacts and the cytoskeleton were also affected, as evidenced by a regulation of the expression of b-actin and tubulin.…”
Section: Discussionsupporting
confidence: 61%
“…45 However, one study had opposite results that silver nanoparticles could increase the GJIC in A549 cells through upregulation of Cx43 protein level, suggesting that silver nanoparticles might target GJIC and Cx43 for their biological effects. 46 In the present study, the SNPs used had a negative effect on GJIC. We found that SNPs inhibit GJIC in a concentration-dependent manner in H9c2 cells, in addition to causing downregulation of the gap junctional channel protein Cx43 in a concentration-dependent manner after SNPs treatment with upregulation of the level of P-Cx43.…”
mentioning
confidence: 89%